2022
DOI: 10.1002/jmri.28432
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Evaluation of Type B Aortic Dissection Using Compressed Sensing Accelerated 4D Flow MRI

Abstract: Background 4D Flow MRI is a quantitative imaging technique to evaluate blood flow patterns; however, it is unclear how compressed sensing (CS) acceleration would impact aortic hemodynamic quantification in type B aortic dissection (TBAD). Purpose To investigate CS‐accelerated 4D Flow MRI performance compared to GRAPP‐accelerated 4D Flow MRI (GRAPPA) to evaluate aortic hemodynamics in TBAD. Study Type Prospective. Population Twelve TBAD patients, two volunteers. Field Strength/Sequence 1.5T, 3D time‐resolved ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…One possible reason for the temporal relationship between acute deterioration and hypotension is the vulnerability of the dissected vessel or false lumen and the distribution of blood flow between the true and false lumens. Recently, 4D-flow MRI has been used to evaluate the haemodynamics AAD [18], and a study by Armour et al [19]. using a pig model suggested that an increase in the flow rate in the true lumen is associated with a decrease in wall shear stress around the tear from changes in local velocity, resulting in a decrease in false luminal pressure and the pressure difference between the two lumens, suggesting aortic stabilisation [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason for the temporal relationship between acute deterioration and hypotension is the vulnerability of the dissected vessel or false lumen and the distribution of blood flow between the true and false lumens. Recently, 4D-flow MRI has been used to evaluate the haemodynamics AAD [18], and a study by Armour et al [19]. using a pig model suggested that an increase in the flow rate in the true lumen is associated with a decrease in wall shear stress around the tear from changes in local velocity, resulting in a decrease in false luminal pressure and the pressure difference between the two lumens, suggesting aortic stabilisation [19].…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for the temporal relationship between acute deterioration and hypotension is the vulnerability of the dissected vessel or false lumen and the distribution of blood flow between the true and false lumens. Recently, 4D-flow MRI has been used to evaluate the haemodynamics of AAD [18], and a study by Armour et al . [19].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of CS and Deep Learning, the networkbased CS methods have been applied to magnetic resonance imaging (Kilinc et al, 2022), acoustic transmission (Atanackovic et al, 2020), and synthetic aperture radar imaging (Cheng et al, 2022). The network-based CS method allows the reconstruction of images quickly once the network has been trained.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we investigated the applicability of the CS-accelerated SV 4D flow MRI in TBAD with no impact by the DV methodology [31]. Here, in this study, we aim to systematically evaluate the potential utility of CS-accelerated DV 4D flow MRI with an acceleration level of 7.7 (R = 7.7) in aortic hemodynamics, including KE, PV, forward flow (FF), reverse flow (RF) and flow stasis in a cohort of chronic TBAD patients and volunteers.…”
Section: Introductionmentioning
confidence: 99%